1999
DOI: 10.1111/j.1744-6155.1999.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Broken Past, Fragile Future: Personal Stories of High‐Risk Adolescent Mothers

Abstract: purpose. To uncover what adolescent mothers view as their childhood struggles, their transition to the role of motherhood following a childhood of abuse/neglect, and their important relationships after they became parents. design. Qualitative, phenomenological. setting. Community‐based parenting program for first‐time mothers at risk for abusing or neglecting their children. participants. Seven first‐time mothers, ages 13 to 20, who reported they had been abused and/or neglected as children. All had healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…It may be that the participants in Clifford and Brykczynski's study had different perceptions because they had already delivered their babies and were parenting, whereas the participants in the study reported here were still pregnant at the time of the interview. Williams and Vines (1999) conducted a phenomenological study to identify what adolescent mothers view as their childhood struggles, transition to the role of mother, past history of abuse and neglect, and important relationships after they became pregnant. Participants identified five themes: an impoverished past, disintegration of relationships, emotional distance, problem-fixing, and reconnecting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that the participants in Clifford and Brykczynski's study had different perceptions because they had already delivered their babies and were parenting, whereas the participants in the study reported here were still pregnant at the time of the interview. Williams and Vines (1999) conducted a phenomenological study to identify what adolescent mothers view as their childhood struggles, transition to the role of mother, past history of abuse and neglect, and important relationships after they became pregnant. Participants identified five themes: an impoverished past, disintegration of relationships, emotional distance, problem-fixing, and reconnecting.…”
Section: Discussionmentioning
confidence: 99%
“…Seven adolescent mothers between the ages of 13 and 20 years identified five themes: an impoverished past, disintegration of relationships, emotional distance, problem fixing, and reconnecting. Participants reported using the pregnancy as a way to grow individually (Williams & Vines, 1999). Their pregnancy experience was viewed as a ''second chance'' for a new life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been suggested that pregnancy among troubled youth, including those on the streets, may be welcomed as a time for positive change. 31,32 In our assessment, we found that four of ten females and three of ten males reported that their most recent LPI was intended. This finding might reflect inclusion of older age (20-24 years) street youth in our sample or the desire of youth to use pregnancy as a way to improve one's life trajectory, as at least two qualitative studies have reported that pregnancy motivated homeless youth to secure housing.…”
Section: Discussionmentioning
confidence: 70%
“…Adolescents who become pregnant require unique consideration, understanding, care, and support during their first pregnancy (American Academy of Child and Adolescent Psychiatry, 1997; Bushy, 2000). First-time teenage mothers undergo physiological, psychological, and emotional changes during their transition to motherhood (Carter & Spear, 2002;SmithBattle, 1997;SmithBattle & Leonard, 1998;Trad, 1995;Williams & Vines, 1999). As a result, researchers have asserted that health care professionals must utilize an alternative view of teenage childbearing in planning their care (Geronimus, 1997;SmithBattle & Leonard, 1998).…”
Section: Theoretical Frameworkmentioning
confidence: 99%